Tobacco Use Worldwide: Legislative Efforts to Curb Consumption - M. Teresa Perez-Warnisher; M. del Pilar Carballosa de Miguel; Luis M. Seijo (Ubiquity Press, 2018)
Tobacco smoking is recognized as a major preventable cause of disease worldwide and is linked to 6 million deaths annually, 30% of which are due to cancer. The negative health consequences of smoking currently represent one of the greatest public health challenges. Secondhand smoke, declared carcinogenic by the International Agency for Research on Cancer in 2004, is also a major source of morbidity and premature death in nonsmokers, particularly children. Negative health effects associated with exposure to secondhand smoke have been well documented and include lung cancer, cardiovascular disease, asthma, and other respiratory diseases. International and national policies to implement cost-effective strategies to curtail smoking will have a significant impact on population health and will protect nonsmokers. Effective interventions, such as a combination of smoke-free laws, tobacco price increases, easy access to tobacco cessation treatments, and anti-tobacco media campaigns, should continue. Reducing tobacco use would be a major step towards the goal of decreasing health disparities by 2030 as 80% of the projected tobacco-related deaths will occur in low- and middle-income countries.